As provas da imortalidade da alma no Livro I das Discussões Tusculanas de Cícero - Borges, Lucas Nogueira (2016)
This dissertation aims at presenting and discussing the proofs for immortality of the soul in Book I of the Tusculan Disputations by Cicero, a philosophical work written in the form of a dialogue in which why man must not fear death is discussed. Before directly approaching the theme, in the proem to Book I, Cicero presents his conception about philosophy and about the requirement of producing philosophy in Latin. Concerning its subject, the dialogue of Book 1 can be divided into two great parts: the first one consisting of an argumentation favourable to the immortality of the soul, that proves death is something good (18-71), and the second one, consisting of a reservation that death is not only something good, but it cannot be something bad (82-119). In accordance to the main goal of this work and based on several different translations which allowed us to do the work with a philological stance where necessary, and which guided a great part of our investigation through notes and valued suggestions of a secondary bibliography we analysed the first part of Book 1, showing that the argumentation in favour of the immortality of the soul, is according to Cicero, absolute and praiseworthy to the best philosophers. We also noticed that the immortality of the soul had been denied as an axiom of ancient philosophy by Hellenistic thought, such as Stoicism and Epicureanism. Cicero refuses the Stoic views about duration of the souls and despises the Epicurean concept on the proof of the mortality of the soul. There are four proofs of immortality of the soul in Book 1, in which we can find the following discussions: the argument consensus omnium gentium, the soul as warm air, the soul as the principle of movement and the soul as the fifth nature (quinta natura). For this work the last discussions are the most important ones: the discussion of the soul as a principle of movement, from Phaidro by Plato and the discussion of the soul as the fifth nature from the lost dialogues of Aristotle, by means of which, Cicero demonstrates that the soul is eternal and divine, thus, establishing a difference between the nature of the soul and the nature of the body. As it may be seen in the conclusion of this work, the immortality of the soul is restricted to the mind, a part of the soul, provided with reason. Remaining after death of the material body, the soul owns perception and intelligence, as it presents the same nature of god, thus pertaining to the celestial realms.